In five years - Serle, Rebecca ([Waterville, Maine] : Thorndike Press, a part of Gale, a Cengage Company, 2020)
"Where do you see yourself in five years? When Type-A Manhattan lawyer Dannie Cohan is asked this interview question, she has a meticulously crafted answer for it. Later, a newly engaged Dannie goes to sleep confident in her five-year plan. But then she wakes up in a different apartment, with a different ring, and beside a very different man. She discovers that it's 2025, five years in the future. After an intense, shocking hour, Dannie wakes again, now back in 2020. What happened felt like much more than a dream, but she is determined to ignore the odd experience--until four-and-a-half years later, when Dannie meets the very same man from her long-ago vision."--Provided by publisher.
A novel.
Keywords: Women lawyers -- Fiction; Time travel -- Fiction; Life change events -- Fiction; Self-realization in women -- Fiction; Man-woman relationships -- Fiction; Manhattan (New York, N.Y.) -- Fiction; Time-travel fiction; Romance fiction; Large type books